Iranian foreign policy towards Syria (a study in pillars and means) - Al-Araji, Assist. Prof. Dr Salman Ali Hussein (The International and Political Journal, 2023)
The development of the Syrian crisis and its transformation into a war has imposed new challenges on Iran. This development may lead to the fall of one of its allies in the Arab Levant, and this in turn will negatively affect its communication with Hezbollah and the Palestinian resistance factions loyal to it. It also creates obstacles to Iranian influence in the region and affects Syria’s relationship with Hezbollah in the event of the collapse of the Syrian regime, of which Lebanon is a natural geographical extension. Iran’s relationship with Hezbollah is of great importance, as it facilitates the transit of weapons and armed groups, whether from Iran or even from the Syrian people themselves. For these reasons, Iran moved towards Syria through several means and mechanisms, whether economic, military, or even cultural, in order to maintain its presence in the Middle East and its extensions to support the Palestinian resistance factions.